The Relationship of Parental Attachment Patterns to Premarital Sexual Behavior Tendencies of College Students in Asia, Africa, and Australia - Achmad Reza Pahlevi; Fazila Akrami; Mary Gregory; Kristi Kõiv; Sveta Berdibayeva; Garth Lipps; Deborah Yazhini Charles; Shupikai Zebron (Journal of Social and Humanities, 2025)
Cases of students having premarital sex often occur in various places in Indonesia and the world. This has a bad impact on mental health, especially for students. One of the factors that causes the high percentage of premarital sex among students is the lack of parental supervision. This study aims to analyze the relationship between patterns attachment parents on premarital sexual behavior of students in Asia, Africa, and Australia. The variables used in this study are patterns attachment parents and the tendency of premarital sex in students in Asia Africa, and Australia. Respondents consisted of 200 students who were then selected based on the researcher's criteria so that the sampling technique used was purposive sampling. The analysis was carried out using the Pearson Correlations value, the Pearson Correlation value was obtained at -0.713 with a significant value of 0.008, which indicates a negative and significant relationship so that the relationship between the pattern attachment parents towards the tendency of premarital sexual behavior to be accepted. This means that the higher the tendency of the pattern attachment parents, the tendency for premarital sexual behavior to be lower.